2017
DOI: 10.1002/jmrs.238
|View full text |Cite
|
Sign up to set email alerts
|

Rectal protection in prostate stereotactic radiotherapy: a retrospective exploratory analysis of two rectal displacement devices

Abstract: IntroductionHigh rectal doses are associated with increased toxicity. A rectal displacement device (RDD) reduces rectal dose in prostate stereotactic body radiation therapy (SBRT). This study investigates any dosimetric difference between two methods of rectal displacement (Rectafix and SpaceOAR) for prostate SBRT.MethodsRectal dosimetry of 45 men who received SBRT within the PROMETHEUS trial was retrospectively examined, across two radiation therapy centres using the two RDD's. Men received a total dose (TD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…This may reflect more of a self-limiting, peripheral neuropathy rather than mucosal effects. Regarding the method of rectal displacement we have previously reported that SpaceOAR and Rectafix provide similar dosimetric advantages in terms of rectal sparing (19). SpaceOAR was associated with less discomfort and has the added advantage of being in situ for the fractionated component of treatment; however, the additional cost is not routinely covered in Australia currently and there is a small risk of inadequate separation.…”
Section: Discussionmentioning
confidence: 96%
“…This may reflect more of a self-limiting, peripheral neuropathy rather than mucosal effects. Regarding the method of rectal displacement we have previously reported that SpaceOAR and Rectafix provide similar dosimetric advantages in terms of rectal sparing (19). SpaceOAR was associated with less discomfort and has the added advantage of being in situ for the fractionated component of treatment; however, the additional cost is not routinely covered in Australia currently and there is a small risk of inadequate separation.…”
Section: Discussionmentioning
confidence: 96%
“…For treatment mDSS, the proportion between the number of treatment options and the decision support tools remains somewhat skewed. Nguyen et al (2009)[50] suggested 15 different combinations of treatment options, and this did not include the use of rectal displacement devices [65, 66] or proton therapy. The treatment mDSS that were found by the current study primarily involved RT, including treatment plan selection [46], proton compared to photon therapy [49], SBRT compared to IMRT [43], and the use of an implantable rectum spacer in EBRT [47].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogel spacer use in prostate SBRT was documented as early as 2013 by Alongi et al and continues to represent a growing proportion of SpaceOAR utilization [ 11 , 24 , 25 ]. Yet as of this study, the only published phase III randomized prostate hydrogel data were obtained in the conventionally fractionated setting [ 22 ].…”
Section: Discussionmentioning
confidence: 99%